Costa Rica: Facing the International Crisis in an Electoral Year - Villarreal F., Evelyn; Gómez A., Steffan (Revista de Ciencia Política, 2020)
The political dynamic of Costa Rica in 2009 was focused on three main areas: the impact of the international economic crisis, the discussion over electoral processes in the lead up to national elections in February 2010 and the follow ups and new corruption scandals of high authorities. Firstly, the government was primarily focused on the implementation of the ‘Anti-crisis’ Plan, but was also called upon to direct important efforts in response to unforeseen events, such as the emergency aftermath of the earthquake of 8 January, the Al HI swine flu pandemic, and, in the second half of the year, the request made of President Oscar Arias to intervene as a mediator in the Honduran crisis. Second, in the elections of February 2010, and under the new Electoral Code, the candidate for the PLN, the party of government, was duly elected President of the Republic with a popular vote of 46.9 percent. For the first time in the country’s history, the presidency is held by a woman. Finally, in the area of accountability, in the midst of the electoral campaign, new scandals continued to envelop public servants, including the misuse of state institutions’ helicopters and planes for personal matters. Of particular note is the culmination of the first judicial process against the Ex-President Rafael Angel Calderón, who was condemned to five years in prison by a Criminal Court.